Pemanfaatan Limbah Bulu Ayam Sebagai Material Panel Dinding Ramah Lingkungan Sebagai Bentuk Penerapan MBKM - Faharuddin, Ansarullah; Hartono, Sriwijanaka; Thahir Sarkawi, Mukhtar (Window of Community Dedication Journal, 2021)
The existence of Chicken Feather which is a waste from a chicken slaughterhouse that is produced every day and still not widely used. The quantity of chicken feather waste is currently quite large because the purchasing demand and public needs in consuming chicken meat are very high, starting from the middle class to the upper class. It can be seen that from restaurants to roadside stalls, their main menu cannot be separated from chicken meat. This will cause considerable waste and if not utilized or processed will cause in environmental pollution, unpleasant odors. According to that, researchers and teams involving students did community service with partners providing socialization to residents and chicken slaughterhouse business actors, that waste from chicken feathers can be used as building materials in the form of economical and environmentally friendly wall panel materials. This community service aimed to socialize the benefits of chicken feather waste as wall panel material to residents with the program for the implementation of the Merdeka Learning Campus Merdeka (MBKM) and community resource empowerment and development.